THE INFLUENCE OF PRODUCT QUALITY AND PERCEIVED VALUE, MEDIATED BY BRAND TRUST ON CONVERTING MACHINE PURCHASE DECISIONS IN INDONESIA’S FLEXIBLE PACKAGING INDUSTRY - Indra Mandala; Bernard Tirto Widjaja; Saparso (CV. RADJA PUBLIKA, 2024)
This research aims to analyze purchasing decisions for flexible packaging converting machines involving the influence of product quality and perceived value mediated by brand trust. Data were obtained using census techniques with the entire population as a research sample from 22 companies in Indonesia's flexible packaging industry that have used SBP brand converting machines, then analyzed using PLS-SEM SmartPLS 4 based on the p-value. The results indicate that the product quality variable does not have a significant effect on brand trust and purchasing decisions. The perceived value variable has a positive effect on brand trust and purchasing decisions. As an independent variable, the brand trust variable has a positive effect on purchasing decisions. However, the brand trust variable is unable to mediate the variables of product quality and perceived value on purchasing decisions